+0  
 
0
94
1
avatar+2509 

Help 14

NotSoSmart  Mar 21, 2018
 #1
avatar+87657 
+1

Vertex  ( -2, 5 )    focus  (-2, 6)

 

The parabola opens upward since the focus is above the vertex

 

p  =  the distance from the vertex to the focus  =  1

 

So  we have

 

4p(y - 5) = (x - ( -2))^2

 

4(1)(y - 5)  =  ( x + 2)^2

 

4 ( y - 5)  = ( x + 2) ^2        divide both sides by 4

 

y - 5 =  (1/4)(x + 2)^2       add 5 to both sides

 

y  = (1/4) (x + 2)^2   + 5

 

 

 

cool cool cool

CPhill  Mar 21, 2018

12 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.